PENGARUH PELATIHAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA UMKM DI BEKASI - Syuhud Akbar; Dudi Duta Akbar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the era of digitalization and globalization, human resource (HR) development has become a key factor in the success and sustainability of organizations. Saga Social Space, despite being newly established for two years, faces challenges in enhancing employee skills through systematic job training and creating a conducive work environment. This study aims to analyze the effect of job training and work environment on employee performance at Saga Social Space in Bekasi. The research employs a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to 34 employees and processed using SPSS version 25 software. The analysis techniques include data quality tests, classical assumption tests, hypothesis tests, and coefficient of determination tests. The results show that job training has no significant effect on employee performance, while the work environment has a significant effect on employee performance. Simultaneously, job training and work environment have a positive effect on employee performance. The novelty of this research lies in the in-depth analysis of the simultaneous influence of job training and work environment on employee performance in the context of SMEs in Bekasi, which has not been extensively studied before.